Oriented teaching in stricto sensu training in nursing before and during the pandemic: an experience report (Research, Society and Development, 2021)
Objective: To report on the teaching practice of master's/doctoral students in their Guided Teaching Assignments from the year 2014 to the year 2021, facing the discipline of Nursing Practice A and B contained in the Pedagogical Project of an Undergraduate Course in Nursing before and during the pandemic of COVID-19.  Method: This is an experience report of master's and doctoral students of the Graduate Nursing Program of the Federal University of Santa Maria (UFSM), located in southern Brazil. The experiences of the teaching praxis of the authors from the year 2014 to the year 2021 are described, about the planning and development of the subjects of Exercises A and B contained in the Pedagogical Project of the Undergraduate Course in Nursing of the institution, taught through Guided Teaching I and II, before and during the pandemic of COVID-19. Results: for the development of the teaching practice, several teaching and assessment methodologies and didactic materials were used, such as: videos, films, case studies, educational games, portfolios and seminars. In the context of the pandemic, there was a need to adapt the classes to remote teaching, providing a unique experience to stricto sensu students. Conclusion: guided teaching activities are essential for teacher training, as they allow the graduate student to reflect and act upon the planning and conduct of teaching activities, as well as the educational readjustments required with the COVID-19 pandemic.